Rough Prime Ideals in -Semirings - Subha, V.S (Universal Research Reports, 2017)
In this paper we introduce the notion of rough prime ideals, rough semi-prime ideals, strongly rough irreducible ideals and rough irreducible ideals of -semirings and discuss some of its properties.